Genesis and Evolution of National Costume - Akhmetshina, Gulnaz Radikovna; Karamova, Klara Khakimovna; Muksinov, Ravil Munirovich (International Journal of Criminology and Sociology, 2022)
This study is devoted to the analysis of the foundations of the development and preservation of the national costume from the moment it appeared with justified exceptional characteristics and further modification due to its relationship with various factors and its use in modern times. The effects of geographical, natural, historical, cultural, economic and social factors are considered. The dynamics of the development of the Tatar national costume is revealed from the point of view of decorative and applied folk art. Also, the potential of folk art in the aspect of enriching professional design and identifying new popular solutions in the design of clothing is revealed. Examples of the appeal of fashion designers to the cultural heritage of their ancestors are given. The article focuses on the national costume in contemporary art. We ask what the modern clothes of the Tatars are and whether there is a national trait inherent in the people and reflected in Tatars’ appearance. First of all, we need to consider that clothes are divided into everyday and festive looks. And one cannot but take into account such a vivid translator of national culture as a stage or theater costume. In addition, when narrating about the trends of modern Tatar fashion, one must take into account the following aspect: general Muslim and national Tatar trends in style, which is especially pronounced in women's clothing.